Cutaneous Anthrax in Gunung Kidul, Yogyakarta: A Case Report - Riswanto, Riswanto; Redhono, Dhani; Nurhayatun, Evi (Jurnal Penyakit Dalam Indonesia, 2021)
Bacillus anthracis is an aerobic, gram-positive, and spore-forming Bacillus species. The most common form of anthrax infection is the cutaneous form. The infection usually develops several days after exposure to products of infected animals and manifest as a black sore with severe swelling on the skin. In this report, a 60-year-old man with a black and swollen lesion on her index finger presented in Gunung Kidul in December 2019. ELISA antibody anthrax serum was performed. The patient was then treated with antibiotics after diagnosis. This patient had a history of contact with the beef of a slaughtered sheep. The patient was treated after making a correct and rapid diagnosis and sufficient antibiotic therapy. We presented this case to update our information about cutaneous anthrax, which are become a current issue again. With appropriate management, cutaneous anthrax can heal with a good result.